Design Considerations for a Florida-Friendly Demonstration Landscape: A Case Study for Student and Extension Volunteer Involvement - Gail Hansen; Brian Niemann (EDIS)
Landscape design students in the Environmental Horticulture Department at the University of Florida participated in the planning and design of the landscape for a new professional development center on the university campus. Such large-scale projects provide a unique experiential learning activity for students and volunteers in landscape design and horticulture programs. This 6-page fact sheet was written by Gail Hansen and Brian Niemann, and published by the UF Department of Environmental Horticulture, August 2012.